Exploring the Representations of Caste and Ethnic Relations in Nepali Short Stories - Budhathoki, Mahendra Kumar (Cognition, 2022)
Hindu society has different castes although the exact date of the origin of caste system is not known. Literary writers depict characters of different castes representing a Hindu society. This paper explored the representations of castes and ethnic relations in Hindu society presented in Nepali short stories. The writers have not prioritized more on the themes of castes, but depicted the interactions and interdependence of various castes to expose the other themes. To explore the representations of castes in Nepali short stories, a few representative short stories translated into English are randomly selected; the qualitative descriptive method was exploited to discuss the stories. The findings of the study are that the interactions and interdependence of characters from different castes produce the distinctive themes of the stories. The writers gave good names like Deviraman, Sitaram Pandit, Padmanidhi Lamichhane to upper caste characters, but exotic names like Chame, Juthe, Lukhure, etc. to so-called lower. Upper caste the Dware exploits a lower caste person Lukhure. The upper caste characters dominate the lower castes. Thus different castes are portrayed in the stories to squeeze the themes. Understanding the representations of castes in literature aids to analyse the condition of castes in the Hindu society.